2018
DOI: 10.21037/jtd.2018.02.59
|View full text |Cite
|
Sign up to set email alerts
|

Is closed thoracic drainage tube necessary for minimally invasive thoracoscopic-esophagectomy?

Abstract: Background: Closed thoracic drainage tube (CTDT) is a conventional treatment after esophagectomy, even after minimally invasive esophagectomy. Here, we report a single-center, retrospective study to explore the safety and necessity of CTDT after thoracoscopic-esophagectomy. Conclusions: This study demonstrated that the treatment of no-CTDT after the minimally invasive thoracoscopic-esophagectomy is safe and feasible, might reduce the work intensity of medical stuff and lead to a better patients' experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The use of closed thoracic drainage tubes after esophageal cancer surgery has been shown to aid in the removal of extra uid and gas, promote lung lobe recruitment, and reduce the risk of postoperative lung infections. However, the conventional wisdom has been to use thicker diameter drainage tubes to improve drainage effectiveness 10,11 . In this section, we will discuss recent research on the use of central venous catheters for thoracic drainage, including their advantages, disadvantages, and potential complications 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of closed thoracic drainage tubes after esophageal cancer surgery has been shown to aid in the removal of extra uid and gas, promote lung lobe recruitment, and reduce the risk of postoperative lung infections. However, the conventional wisdom has been to use thicker diameter drainage tubes to improve drainage effectiveness 10,11 . In this section, we will discuss recent research on the use of central venous catheters for thoracic drainage, including their advantages, disadvantages, and potential complications 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the use of single versus two chest drains after oesophagectomy, retrospective studies 50–52 have suggested equivalence in terms of respiratory complications, but a reduction in pain scores with fewer drains 50 , 51 . Similarly, transhiatal drain placement may result in lower pain scores and analgesia use 52–54 , without any significant differences in respiratory or other complications.…”
Section: Resultsmentioning
confidence: 99%
“…The postoperative employment of closed thoracic drainage tubes in esophageal cancer surgeries has been substantiated to aid in the expulsion of extraneous fluid and gas, invigorate lung lobe recruitment, and mitigate the probability of subsequent pulmonary infections. Despite this, conventional wisdom advocates for the application of broader diameter drainage tubes to augment the proficiency of drainage [ 12 , 13 ]. Our investigation has uncovered numerous merits of adopting a Central Venous Catheter (CVC) for thoracic drainage in patients subjected to minimally invasive esophageal cancer surgery instead of traditional closed thoracic drainage.…”
Section: Discussionmentioning
confidence: 99%